An Analysis Of Floor Plate Reinforcement Structure Calculation Plan On Irian Supermarket Building Road Of Setia Budi Medan - Yosua Hot Rejeki Tamba; Darlina Tanjung (Jurnal Scientia, 2024)
The increasing number of tall buildings being built in the modern era now. Making it increasingly important to calculate accurate and comprehensive structures in accordance with applicable regulations, especially the Indonesian National Standard (SNI) and of course the building to be built is safe from all potential structural failures and the most efficient reinforcement used. In the Irian Supermarket Building project, Setia Budi Medan, an analysis of the level of safety of the floor slab structure is required in accordance with SNI 2847-2019 and an analysis of the most efficient reinforcement that can be used in the floor slab structure of the Irian Supermarket Building, Setia Budi Medan. And the formulation of the problem discussed is the level of safety of the building structure and the most efficient reinforcement that can be used. The research method is carried out using the case study method where the collection of field data and additional data, data is processed in accordance with SNI 2847-2019 and for reinforcement efficiency is done by increasing the distance between the reinforcements. The result is the value of As needed: 652.4 mm2 < As used: 670.4 mm2 for flexural reinforcement (2Ø8-150) and As needed: 455.4 mm2 < As used: 502.4 mm2 for shear reinforcement (2Ø8-200) so that the reinforcement used is safe to use while the total deflection: 16.6 mm > allowable deflection: 6.68 mm and ϕVc: 58650 N/mm > Vu: 32823.07 N/mm so that the thickness of the plate used is 120 mm safe to use. However, reinforcement efficiency cannot be done because the value of As needed: 652.4 mm2 > As used: 455.4 mm2 for flexural reinforcement (2Ø8-200) and As needed: 455.4 mm2 > As used: 401.92 mm2 for shear reinforcement (2Ø8-250) so that reinforcement efficiency cannot be carried out.